Multiple left anterior descending coronary artery to left ventricular fistula - A case series and literature review - Praneet Iyer; Rishitha Yelisetti (Greater Baltimore Medical Center, 2017)
Coronary artery fistulas (CAFs) are found in 0.3-0.8% of patients who undergo coronary angiography. CAFs are defined as single or multiple, small or large direct communications that arise from one or more coronary arteries and enter into one of the four cardiac chambers or major vessels. We present two cases of multiple coronary artery fistulas arising from diagonal and left anterior descending (LAD) branches of left coronary artery draining into the left ventricle. In both the cases, No intervention was performed. Of the congenital fistulas, two major groups are identified: solitary CAFs or coronary artery-left ventricular multiple micro-fistulas (CALVMMFs). Noninvasive techniques such as transthoracic echocardiography, transesophageal echocardiography and magnetic resonance imaging are becoming increasingly popular for diagnosis and follow-up of CAFs. Despite the advent of these newer non-invasive modalities, coronary angiography remains the gold standard for diagnosis. Treatment of CAFs is indicated when the patients are symptomatic with left ventricular volume overload, myocardial ischemia, left ventricular dysfunction or in the presence of a large or increasing left-to-right shunt. If the fistula is small and hemodynamically insignificant, it can be managed with conservative management. Multiple left anterior descending to left ventricle (LV) fistulas are extremely rare and, as per our literature review, we noted only a few case reports of coronary artery fistulas between branches of LAD and left ventricle.